Luther's Ecclesiology and His Concept of the Prince as Notbischof - Spitz, Lewis William 1922-1999 (1953)
Until the appearance of Rudolf Sohm's Kirchenrecht in 1892 and of Karl Rieker's study, Die rechtliche Stellung der evangelischen Kirche Deutschlands in ihrer geschichtlichen Entwicklung bis zur Gegenwart in 1893, the opinion prevailed among scholars by and large that the historic development in the relationship of the church in Germany to the state was contrary to the ideal of the Reformer. This ideal was held to be an autonomous congregational church based upon evangelical principles, an interpretation which had received the support of Aemil Richter's authority in Die Geschichte der cvangelischen Kirciwnverfassung in Deutschland, 1851. Since then, Reformation students have divided on this question. Luther wrote of the Notbischöfe: “I wish to leave the jurists … to settle this disputation … I will write as a theologian and a heretic,” and thereby he left a legacy of controversy both to jurists and historians. With equal truth Luther could write, “The other articles … I commend to the lawyers, for it is not my business as an evangelist to decide and judge in these matters. I shall instruct and teach consciences what pertains to divine and Christian matters,” and still maintain, “that since the time of the apostles the secular sword and authority has never been so clearly described and grandly lauded as by me, which even my enemies must acknowledge.” He was involved by circumstances in social and political questions which were not per se his concern as a theologian. Several factors complicate an analysis of Luther's theory of church and state, the immediacy of the medieval inheritance, conceptual differences of terminology from current usage, the complexity of the transitional historical situation, and Luther's characteristic way of addressing himself to a problem without relating his plan of action to his total theory. In fact, Dieckhoff says that as the pertinent quotations lie side by side, it is impossible to harmonize them. Such pessimism, however, is unwarranted, for Luther was never pathologically dialectical and his position can be satisfactorily understood if viewed in relation to his central orientation. Luther's political theory involved, of course, many facets, the question of Imperial power, papal theory, war, toleration, the Turkish question, feudal loyalties, and others. A study of the Notbischöfe problem is central, however, for an understanding of his ecclesiology and the much debated church-state question.
Keywords: Luther,Martin; Verhältnis Staat-Kirche; Ekklesiologie; church-state relations; Ecclesiology